Peningkatan Peningkatan Kemampuan Menulis dan Berpikir Kritis melalui Pemetaan Pikiran Visual Digital di Kelas Menulis - S, Khafifah Indar Parawansa; Moh. Hafidz (Global Action and Education for Society, 2025)
This study aims to determine the use, application and effect of digital visual mind mapping method on narrative text learning of MA Al Hidayah Bangkalan students. This research uses a qualitative design. The design used is a qualitative design. The instruments used by researchers are observation, interviews and documentation. The participants in this study were 1 teacher who taught English class XI at MA Al Hidayah Bangkalan. The observation result shows that learning using digital visual mind mapping creates an active, interactive, interesting and fun learning environment because students exchange opinions and build cohesiveness between teams. After conducting an interview with the teacher concerned, it can be seen that the application of the digital visual mind mapping method is very effective and can make students faster in understanding lessons through things that students really like and also motivate students to be more enthusiastic and train students' critical thinking skills. Although there are some students who are still shy and find it difficult due to the lack of vocabulary they have, the digital visual mind mapping method can make them more free to express ideas into writing. The results of the documentation as evidence and digital traces of the application of the method. The findings of this study show that the visual mind mapping method is a method that fits the needs of students today and facilitates students in writing activities and hones students' critical thinking skills.